Multi-stakeholder perspective on community pharmacy services in Saudi Arabia: A systematic review and meta-analyses for 2010–2020 - Khalid S. Alghamdi; Max Petzold; Mahdi H. Alsugoor; Hafiz A. Makeen; Christina Ljungberg Persson; Laith Hussain-Alkhateeb (Exploratory Research in Clinical and Social Pharmacy)
Background: Community pharmacists are the third-largest group of healthcare professionals globally; their capacity often extends far beyond dispensing medication, and they are increasingly involved in a diverse range of advanced health service delivery, which can potentially improve public health outcomes. Among the many initiatives of the Saudi national transformation program towards Saudi Vision 2030 are plans to transform the current model of community pharmacy services by expanding their role to include patient-centered healthcare provision. Objectives: This systematic literature review (2010−2020) of the multi-stakeholder perspective aimed to evaluate services provided by Saudi community pharmacies and satisfaction levels, investigate perceived factors associated with the practice, and identify barriers affecting services. Materials and methods: Seven scientific electronic databases were searched. The review was conducted in accordance with PRISMA guidelines. This review was subjected to descriptive analyses, meta-analyses of proportion, and narrative synthesis. The Mixed Methods Appraisal Tool version 2018 was used to assess the quality of studies. Results: Minimal physician participation, community pharmacies' owners and managers, and gender imbalance among pharmacists all arose as gaps in Saudi Arabia. The findings showed that community pharmacies enable self-medication, with one-third of antibiotics being dispensed without prescriptions despite the threat of law enforcement. The deficiency of patient counseling by community pharmacists threatens patient safety, and the lack of knowledge about clinical services diminishes opportunities for adequate practice. Conclusion: Several factors contributing to this inadequate performance and low satisfaction levels were reported. The findings were alarming and highlighted the need to intensify efforts towards Saudi Vision 2030, which aims to improve the overall population health and healthcare system in Saudi Arabia. Our review suggests that more efforts are needed to integrate key commercial, administrative, and technical sectors associated with the processes of community pharmacy dispensing and counseling.